Is real-time dynamic cervical shortening predictive of preterm birth?- A case control study. (17th December 2022) - Rottenstreich, Amihai; Gochman, Neta; Kleinstern, Geffen; Levin, Gabriel; Sompolinsky, Yishay; Rottenstreich, Misgav; Sela, Hen Y.; Yagel, Simcha; Porat, Shay
Abstract: Objectives: We aimed to assess the risk of preterm birth in those with real-time dynamic cervical shortening. Methods: A retrospective matched case-control study. The study group comprised all women with dynamic cervical shortening (≥4 mm) noted from 24 to 34 weeks of gestation during 2010–2017 at a university hospital. Two control groups of women were established by matching the minimal and maximal cervical length measured, as well as age, parity, gestational age, history of spontaneous preterm birth, symptoms of preterm labor, and delivery year. Results: Data from 339 women were analyzed, 113 with dynamic cervical shortening comprised the study group, and two groups with 113 women each, matched for the minimal and maximal cervical lengths measured comprised the control groups. Rates of spontaneous preterm birth rate at <37 weeks (32.7% vs. 15.9%; OR [95% CI]: 2.60 (1.36, 4.87), p = .004) and <35 weeks (15.9% vs. 5.3%; OR [95% CI]: 3.38 (1.29, 8.86), p = .013) were significantly higher among those with dynamic cervix than among the control group matched for the maximal cervical length, and comparable to the control group matched for the minimal cervical length. The negative predictive values of cervical length for preterm birth occurrence at various cutoff values were lower in those with dynamic cervix. Conclusions: The minimal cervical length measured should be used to guide patient management when dynamic cervix is noted. In the setting of dynamic cervical change, the value of cervical length as a negative predictor of preterm birth is limited.